URGENSI CHARACTER BUILDING PADA ANAK SEJAK DINI - Yudi, Dede (Universitas Muhammadiyah Magelang, 2011)
Some of the stain in the world of education in Indonesia at this time include the unfolding corruption case small and the culture of violence that is cheating the form of fighting between students, a higer intensity.